2023
DOI: 10.1002/nop2.1672
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the moral courage of nurses in China: A cross‐sectional study

Abstract: Aim The purpose of this study was to assess the level of moral courage among nurses in China, and to explore related influential factors, to help nursing managers take measures to improve nurses' moral courage. Design A cross‐sectional study. Methods The data adopted a convenient sampling method. From September to December 2021, 583 nurses from five hospitals in Fujian Province completed the Chinese version of the Nurses' Moral Courage Scale (NMCS). Data were analysed using descriptive statistics, chi‐square t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…The results indicated that the level of ethical courage among nurses was at a high level. Similar to the ndings of the present study, studies conducted by Huang et al, Luo et al, and Zheng et al also reported high levels of ethical courage (17)(18)(19). The results of the study by Hakimi et al were also consistent with the present study (20).…”
Section: Discussionsupporting
confidence: 92%
“…The results indicated that the level of ethical courage among nurses was at a high level. Similar to the ndings of the present study, studies conducted by Huang et al, Luo et al, and Zheng et al also reported high levels of ethical courage (17)(18)(19). The results of the study by Hakimi et al were also consistent with the present study (20).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, nurses with higher levels of professional competence reported stronger relationships with their colleagues, likely because they are more likely to be seen as competent and trustworthy [48]. Many research studies have indicated that good interpersonal relationships are an important factor in combating burnout [49,50]. Terefore, higher professional competence can positively contribute to good interpersonal relationships and self-confdence at work, which can then reduce stress and burnout.…”
Section: Improving Professionalmentioning
confidence: 99%